Analisis Proses Berpikir Refraktif dalam Pemecahan Masalah bagi Siswa Ditinjau dari Daya Juang Produktif - Gracia, Gracia; Kriswandani, Kriswandani (Jurnal Pendidikan Matematika : Judika Education, 2024)
This study aims to analyze the refractive thinking process of students in problem solving in terms of the level of productive fighting power. This type of research is qualitative descriptive research. The subjects of this study included 3 students of class X SMA Laboratorium Salatiga who were taken from students who had high, medium, and low fighting power. The research instruments included human instruments (researchers), essay tests in the form of mathematical application problems, namely the problem of delivering goods, field notes, and documentation. The analysis and conclusion stages used data triangulation techniques. The results of this study indicate that the stages of refractive thinking with medium and low fighting power include 5 stages, namely confusion, investigation, constructive activity, evaluation and decision making. The stages of refractive thinking of students with high fighting power include 4 stages, namely investigation, constructive activity, evaluation and decision making. In conclusion, students with high fighting power do not experience confusion (perplexity) in solving mathematical problems and do not need help from others. While students with medium and low fighting power go through all five stages in solving mathematical problems with the help of others. Keywords: Refractive Thinking, Productive Fighting Power, Mathematical Problem Solving